2020
DOI: 10.1167/jov.20.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Looking away from a moving target does not disrupt the way in which the movement toward the target is guided

Abstract: People usually follow a moving object with their gaze if they intend to interact with it. What would happen if they did not? We recorded eye and finger movements while participants moved a cursor toward a moving target. An unpredictable delay in updating the position of the cursor on the basis of that of the invisible finger made it essential to use visual information to guide the finger's ongoing movement. Decreasing the contrast between the cursor and the background from trial to trial made it difficult to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Whereas eye movements are beneficial, they might not always be necessary for accurate interception. For example, when observers were asked to collide their unseen finger (represented by a cursor) with a moving target, they were able to guide interception timing using either foveal or peripheral vision, although large individual differences were noted in this study [30]. Whether accurate eye movements are necessary or merely beneficial might depend on exact task requirements and stimulus environments.…”
Section: Eye Movements Improve Reaching and Interception Performancementioning
confidence: 77%
“…Whereas eye movements are beneficial, they might not always be necessary for accurate interception. For example, when observers were asked to collide their unseen finger (represented by a cursor) with a moving target, they were able to guide interception timing using either foveal or peripheral vision, although large individual differences were noted in this study [30]. Whether accurate eye movements are necessary or merely beneficial might depend on exact task requirements and stimulus environments.…”
Section: Eye Movements Improve Reaching and Interception Performancementioning
confidence: 77%
“…If people want to intercept a target, they are reluctant not to follow it with their eyes (Cámara et al, 2020). This is understandable because they can intercept a target that they are following with their eyes slightly more precisely (Brenner and Smeets, 2011).…”
mentioning
confidence: 99%
“… Diaz, Cooper, Rothkopf, and Hayhoe (2013) suggested that such pursuit might generate extraretinal signals that help predict the future location of the ball. Other studies inferred a useful role for both retinal and extraretinal aspects of pursuit of the target or cursor in tasks that required manual interception of a moving object ( Camara, Lopez-Moliner, Brenner, & de la Malla, 2020 ; Cesqui, Mezzetti, Lacquaniti, & d'Avella, 2015 ; Danion & Flanagan, 2018 ; Fooken, Yeo, Pai & Spering, 2016 ).…”
Section: Introductionmentioning
confidence: 99%